Analysis of the microbiota of pregnant women in relation to weight gain during pregnancy – a pilot study - Kosinska-Kaczynska, Katarzyna; Zgliczynska, Magdalena; Krawczyk, Dominika; Piatkowska, Magdalena; Balabas, Aneta; Czarnowski, Paweł; Goryca, Krzysztof; Glinicki, Piotr; Ostrowski, Jerzy; Zeber-Lubecka, Natalia (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionExcessive body weight was associated with changes in individual microbiota. However, limited research on the impact of excessive gestational weight gain (GWG) revealed that microbiota patterns related to GWG differed from those linked to pregestational overweight or obesity.AimThe aim was to compare differences in the microbiota of women in the third trimester of gestation who had excessive and non-excessive weight gain during pregnancy.Material and methodsWomen with a singleton gestation at 34 + 0 weeks and normal pregestational body mass index were recruited to the study. Patients who were diagnosed with excessive weight gain formed the study group (n=11), while those with non-excessive weight gain formed the control group (n=10).ResultsIn cervico-vaginal samples, bacterial 16S rRNA gene sequencing demonstrated a decrease in alpha diversity, measured with the Shannon index, in the study group compared to the control group. While the difference was not statistically significant after correction for multiple testing, the Chao index showed a persistent trend toward reduced species richness in the study group. In stool samples, we identified 29 genera with differential representation between the groups, including nine overrepresented and ten underrepresented genera. The cervico-vaginal microbiota analysis detected 12 species distinguishing the study group from the controls, with four genera (Ralstonia, Pandoraea, Kocuria, and Rhodobacteraceae unclassified) being more prevalent in the study group. However, in both sites none difference was found to be statistically significant after p-value correction.ConclusionsDespite small sample size, we demonstrated slight trends in microbiota composition between groups. These suggest potential differences in microbial diversity and composition associated with excessive GWG, which supports further investigation.